Specialty Drug Coverage Varies Across Commercial Health Plans In The US - Chambers, James D.; Kim, David D.; Pope, Elle F.; Graff, Jennifer S.; Wilkinson, Colby L.; Neumann, Peter J. (Health Affairs, 2018)
We analyzed specialty drug coverage decisions issued by the largest US commercial health plans to examine variation in coverage and the consistency of those decisions with indications approved by the Food and Drug Administration (FDA). Across 3,417 decisions, 16 percent of the 302 drug-indication pairs were covered the same way by all of the health plans, and 48 percent were covered the same way by 75 percent of the plans. Specifically, 52 percent of the decisions were consistent with the FDA label, 9 percent less restrictive, 2 percent mixed (less restrictive in some ways but more restrictive in others), and 33 percent more restrictive, while 5 percent of the pairs were not covered. Health plans restricted coverage of drugs indicated for cancer less often than they did coverage of drugs indicated for other diseases. Using multivariate regression, we found that several drug-related factors were associated with less restrictive coverage, including indications for orphan diseases or pediatric populations, absence of safety warnings, time on the market, lack of alternatives, and expedited FDA review. Variations in coverage have implications for patients' access to treatment and health system costs.